Regenerative Agronomic Approaches: Technological, Biochemical and Rheological Characterization of Four Perennial Wheat Lines Grown in Italy - Elena Galassi; Chiara Natale; Francesca Nocente; Federica Taddei; Giovanna Visioli; Salvatore Ceccarelli; Gianni Galaverna; Laura Gazza (Agronomy)
Cereals are the basis of the human diet, and among them, after rice and corn, wheat is the most cultivated in the world. Drought, conflicts, and high prices affect food security in many countries. The CHANGE-UP project funded by the PRIMA program aims at redesigning agricultural systems for the Mediterranean area to make them more resilient to climate change, and includes, among other agronomic innovations, the cultivation and characterization of perennial wheat genotypes. In this study, four perennial wheat lines, 235a, 20238, OK72, and 11955, grown in Italy, were examined for their technological and chemical composition and rheological properties and compared with the perennial species Thinopyrum intemedium (Kernza®) and to a modern durum wheat variety, used as controls. On average, all the perennial genotypes presented very small kernels along with high protein content, total antioxidant capacity, and mineral content, and genotypes OK72 and 11955 presented good test weight values. Line 235a had the best gluten quality, whereas line 20238 reported the worst values for bread-making aptitude. Results indicate that perennial grains could adapt to the Italian environment and manifest their nutritional and technological potential, constituting promising raw materials for enhancing diversification in nutrition by sustainable agriculture based on agroecological principles.